2021
DOI: 10.1002/fsn3.2432
|View full text |Cite
|
Sign up to set email alerts
|

The effect of incorporating herbal (Lippia javanica) infusion on the phenolic, physicochemical, and sensorial properties of fruit wine

Abstract: In recent years, there has been an increase of interest in herbal infusions due to the effective promotion of their medicinal properties (Bhebhe et al., 2015). An underutilized indigenous herbal plant, Lippia javanica, has been made popular in many communal homes of Zimbabwe as a tisane (Maroyi, 2017). Lippia javanica (Burm.f.) Spreng belongs to the family Verbenaceae (Figure 1a) and is the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…According to some panelists, the strong taste and aroma of mint in the mixed wine did not combine well with the pitaya wine. Such results are similar to a previous study in which the taste of fruit wine was decreased after the wine was fermented with Lippia javanica extracts (Chawafambira, 2021 ). However, there is limited research focusing on the effect on wine quality, hence, it highlights the importance of bioactive and chemical compounds during fermentation (Singh et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…According to some panelists, the strong taste and aroma of mint in the mixed wine did not combine well with the pitaya wine. Such results are similar to a previous study in which the taste of fruit wine was decreased after the wine was fermented with Lippia javanica extracts (Chawafambira, 2021 ). However, there is limited research focusing on the effect on wine quality, hence, it highlights the importance of bioactive and chemical compounds during fermentation (Singh et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…In another study conducted by Lakicevic et al, selected aromatic herbs were added to red wines from the Serbian autochthonous variety 'Prokupac' (Vitis vinifera L.) and findings indicated that total phenolic and flavonoid contents, along with antioxidant activity, were significantly higher in all examined wine samples [44]. Also, Chamafambria et al showed that the addition of Lippia javanica extracts enhanced the total phenol, color, and sensory properties of a Uapaca kirkiana fruit-based wine [45]. Tarapatskyy et al studied white and red wines of the region of Poland enhanced with cowslip (Primula veris L.) and an increase in polyphenol compounds was detected [46].…”
Section: Discussionmentioning
confidence: 99%
“…Mel/Fok 2020 337. 45 The amount of total phenols that the must extracted from Cannabis sativa, Salvia officinalis and Melissa officinalis during pre-fermentation addition, increased the total phenolic content compared to blank wine 7.97-14.84%, 31.44-42.91%, and 36.68-64.71%, respectively. The same herbs extracted in stable wine (post-fermentation addition) increased the total phenolic content compared to the blank wine 14.47-48.27%, 51.86-91.06% and 75.53-94.53%, respectively.…”
Section: Post-fermentation Herb Addition (In Stable Winementioning
confidence: 95%
“…Fever tea has been reported to have volatile oil as well as various monoterpenoids which include myrcene, caryophyllene, linalool, p-cymene and ipsdienone (Mokoka, 2007;Endris et al, 2016). Endris et al (2016) and Chawafambira (2021), discovered that leaves of fever tea produce numerous polyphenolic compouds such as of stearic, palmitic, myristic, oleic, arachidic, behenic, and lignoceric acids and triacontane alkanes. Misai kucing possess pharmacological properties due to the presence of different groups of phenolic acids including terpenoids (diterpenes and triterpenes) (Abdullah et al, 2020), flavonoids (Pang et al, 2017), and benzochromenes (Abdullah et al, 2020).…”
Section: Huyen 2020mentioning
confidence: 99%